Development of an acellular nerve cap xenograft for neuroma prevention. Issue 11 (17th August 2022) - Faust, Anne E.; Soletti, Lorenzo; Cwalina, Nicole A.; Miller, Andrew D.; Wood, Matthew D.; Mahan, Mark A.; Cheetham, Jonathan; Brown, Bryan N.
Abstract: Neuroma formation following limb amputation is a prevalent and debilitating condition that can deeply affect quality of life and productivity. Several approaches exist to prevent or treat neuromas; however, no approach is either consistently reliable or surgically facile, with high rates of neuroma occurrence and/or recurrence. The present study describes the development and testing of a xenogeneic nerve cap graft made from decellularized porcine nerve. The grafts were tested in vitro for cellular removal, cytotoxicity, mechanical properties, and morphological characteristics. The grafts were then tested in rat sciatic nerve gap reconstruction and nerve amputation models for 8 weeks. Gross morphology, electrophysiology, and histopathology assessments were performed to determine the ability of the grafts to limit pathologic nerve regrowth. In vitro testing showed well decellularized and demyelinated nerve cap graft structures without any cytotoxicity from residual reagents. The grafts had a proximal socket for the proximal nerve stump and longitudinally oriented internal pores. Mechanical and surgical handling properties suggested suitability for implantation as a nerve graft. Following 8 weeks in vivo, the grafts were well integrated with the proximal and distal nerve segments without evidence of fibrotic adhesions to the surrounding tissues or bulbous outgrowth of the nerve. Electrophysiology revealed absence of nerve conduction within the remodeled nerve cap grafts and significant downstream muscle atrophy. Histologic evaluation showed well organized but limited axonal regrowth within the grafts without fibrous overgrowth or neuromatous hypercellularity. These results provide proof of concept for a novel xenograft‐based approach to neuroma prevention.